Pengembangan Media Video Animasi pada Mata Pelajaran IPAS Bab 5 Topik C Kelas V di Sekolah Dasar Negeri 24 Pontianak Kota - Maulana, Arif; Pranata, Rio; Prasodjo, Bayu (ARZUSIN, 2026)
Although animated video-based learning media have received attention in various previous studies, studies that specifically discuss their development in IPAS learning for Chapter 5, Topic C, for Grade V elementary school students based on the Kurikulum Merdeka remain limited. This study aims to produce learning media in the form of animated videos that can be used in the IPAS learning process for Grade V elementary school students. This study used a research and development approach with a product development design, involving 25 Grade V students of SDN 24 Pontianak Kota selected through informant selection. Data were collected through observation and validation, then analyzed using content analysis. The results show that the developed animated video-based learning media were considered feasible for use in IPAS learning. These findings contribute to the development of visual-interactive learning media and broaden understanding of the use of animated videos in supporting IPAS learning in elementary schools. The conclusion of the study affirms that animated videos are relevant as learning media that can support the delivery of material in a more engaging manner and in accordance with the needs of Grade V elementary school students. The implications of this study include theoretical contributions to the development of literature on animated video-based learning media, as well as practical implications for educators in improving the quality of IPAS learning based on the Kurikulum Merdeka. This study also opens opportunities for further research on the effectiveness of animated videos in IPAS learning at the elementary school level.